PENGARUH PENGHARGAAN TERHADAP KINERJA TENAGA TEKNIS KEFARMASIAN PADA RS X DI KOTA BANDUNG - Ani Rahayu; Bunga Destyana Anggun Paramita (Sekolah Tinggi Pariwisata Mataram, 2022)
The main asset that greatly affects the progress of a hospital is human resources (HR). Employees are an asset as well as a driver of creativity and innovation in a company that will increase company profits. In order to achieve company goals, it is necessary to have an award for each individual to work better. This study aims to describe, test and analyze whether the influence of awards, environmental factors, organizational factors and individual factors affect employee performance in the pharmaceutical installation division (pharmaceutical engineering personnel) at hospital X in Bandung City. The sampling technique used survey data using a questionnaire. The sample of this research is pharmaceutical technical staff at hospital X in Bandung, totaling 25 people. The method used is multiple linear regression with the help of SPSs version 24.0. The results of the study show that there is a significant influence between environmental influences, organizational influences, and individual influences on employee performance.